Improving Image Encryption and Decryption Using WU`s Algorithm - Mary Kurian, Simy; Manuel, Nimmymol; Joseph, Neena; George, Neema (International Journal of Computer Sciences and Engineering, 2025)
In this advanced world, pictures are generally utilized in various cycles. Along these lines, the security of picture and information from unapproved utilizes is significant. Presently, data security is turning out to be progressively significant in information capacity and broadcasting. It is fundamental for getting picture, either on the way or store on gadgets. Nonetheless, some picture encryption calculations actually have numerous security issues and can be effortlessly gone after by assailants. This proposed framework plays out the cryptanalysis of a recently proposed variety picture encryption scheme utilizing Wu's algorithms. For encryption plot, typically utilizes a pseudo-irregular encryption key created by a calculation and which makes the picture safer. An approved recipient can without much of a stretch unscramble the message with the mystery key given by the originator to recipient however not to unapproved clients.